Stability of money demand for the Peruvian economy: evaluation of a pretest - Cortez C., Jorge (1988)
​The present paper has a two-foldpurpose: to draw conchisions concerning the stability of the shortten money demand function for the peruvian economy over the period 1976-1987, and to apply contradics the hypothesis of inestability.  In the first section the author summarizes various methodologies to test the stability of parameters, and ends up formulating the TETPE. Secondly, an estion of the short-run money demand function for the peruvian economy is presented. In third place, the author evaluates parameter stability applying the tests explained in section one to the estimates of section two. The paper includes with a summary and a brief discussion of the results. The author suggests ways to overcome some difficulties in further applications.​